Legislative politics in Latin America (Cambridge University Press, 2002)
This theoretically inspired study explores legislative politics in Argentina, Brazil, Chile, and Mexico. Instead of beginning with an assumption that these legislatures are either rubber-stamps or obstructionist bodies, the chapters provide new data and a fresh analytical approach to describe and explain the role of these representative bodies in these consolidating democracies. For each country the book provides three chapters dedicated, in turn, to executive-legislative relations, the legislatures' organizational structure, and the policy process.